Prospective, Multicenter, Randomized, Crossover Clinical Trial Comparing the Safety and Effectiveness of Cooled Radiofrequency Ablation With Corticosteroid Injection in the Management of Knee Pain From Osteoarthritis. Issue 1 (1st January 2018) - Davis, Tim; Loudermilk, Eric; DePalma, Michael; Hunter, Corey; Lindley, David; Patel, Nilesh; Choi, Daniel; Soloman, Marc; Gupta, Anita; Desai, Mehul; Buvanendran, Asokumar; Kapural, Leonardo
Abstract : Background and Objectives: Osteoarthritis (OA) of the knee affects the aging population and has an associated influence on the health care system. Rigorous studies evaluating radiofrequency ablation for OA-related knee pain are lacking. This study compared long-term clinical safety and effectiveness of cooled radiofrequency ablation (CRFA) with intra-articular steroid (IAS) injection in managing OA-related knee pain. Methods: This is a prospective, multicenter, randomized trial with 151 subjects with chronic (≥6 months) knee pain that was unresponsive to conservative modalities. Knee pain (Numeric Rating Scale [NRS]), Oxford Knee Score, overall treatment effect (Global Perceived Effect), analgesic drug use, and adverse events were compared between CRFA and IAS cohorts at 1, 3, and 6 months after intervention. Results: There were no differences in demographics between study groups. At 6 months, the CRFA group had more favorable outcomes in NRS: pain reduction 50% or greater: 74.1% versus 16.2%, P < 0.0001 (25.9% and 83.8% of these study cohorts, respectively, were nonresponders). Mean NRS score reduction was 4.9 ± 2.4 versus 1.3 ± 2.2, P < 0.0001; mean Oxford Knee Score was 35.7 ± 8.8 vs 22.4 ± 8.5, P < 0.0001; mean improved Global Perceived Effect was 91.4% vs 23.9%, P < 0.0001; and mean change in nonopioid medication use was CRFA > IAS ( P = 0.02). There were no procedure-related serious adverse events. Conclusions: This study demonstrates that CRFA is an effective long-term therapeutic option for managing pain and improving physical function and quality of life for patients with painful knee OA when compared with IAS injection. Clinical Trial Registration: ClinicalTrials.gov (NCT02343003 ).